Interactive Android Application as an Assistant to care for Cat’s Health - Roslan, Noor Shameem (UNIVERSITI TEKNOLOGI PETRONAS, 2012)
Cats or domesticated cats have been one of the common pets among Malaysians. It is often called as housecats or simply the cats when there is no need to distinguish it from other felids and felines. Although cats had been ranked as one of the most popular pets among Malaysians besides other domesticated pets, not every individual especially the cat owners will be able to grow a healthy cat. Most of them will wait for their cats to become ill before they think about their health care. In other words, this is a wasteful and dangerous way to ensure a good health for the cats. According to the results of surveys that had been conducted, almost every of the respondents especially those who have and own cats did agreed that financial constraints would be one of the main factors that resist an individual from bringing the cats to the veterinary clinics or hospitals to have health examination and receive the necessary treatments. With the desire to fulfill the tight schedule in everyday’s life, it is impossible for an individual who have null knowledge on cats’ health to glance through the books or the internet in searching for information on how to grow a healthy cat. As a result, with the objective to provide a portable assistant with information and guidance on cats’ health, an interactive Android application will be developed to assist every individual especially cat owners to grow up a healthy cat. This application will eventually cover up every aspects of cats’ health like cats’ diseases diagnosis, information on diseases that will affect the cats, list and steps of first-aids that should be given based on different cases, and basic procedures to give medicine to the cats. Together with this application, since it will be linked to Global Positioning System (GPS), every cat owners can easily identify the locations of veterinary clinics. Interactive Android Application as an Assistant to care for Cat’s Health will be developed based on System Development Life Cycle (SDLC). All of the requirements will be gathered through different methods like distribution of questionnaires to the individuals especially cat owners as well as experts’ interviews.